Localization Preference of Antimicrobial Peptides on Liquid-Disordered Membrane Domains - Su, Juanjuan; Marrink, Siewert J.; Melo, Manuel N. (Frontiers in Cell and Developmental Biology, 2020)
We performed coarse-grained simulations of the antimicrobial peptides Magainin 2, BP100, MSI-103 and MSI-78 on a phase-separated membrane to study their preference for the different domains. All the peptides displayed a clear preference for the liquid-disordered (Ld) phase over the liquid-ordered (Lo) one. For BP100, MSI-103, and MSI-78 there was a further preference of the peptides for the domain interface. The peptides’ preference towards the disordered phase was shown to reflect a penalization of lipid–lipid interaction enthalpy in the Lo phase, when in the vicinity of peptides. Similar results were observed at the two studied concentrations, although Ld phase saturation at the higher concentration drove some of the peptide excess to the Lo phase. Magainin 2 and MSI-103 were found to dimerize, in agreement with available experimental data. Interestingly, at high concentrations of Magainin 2 toroidal pores spontaneously formed in the Ld phase. We performed additional simulations to characterize this phenomenon, which is likely related to Magainin’s membranolytic action.